Isu Etika dalam Pemanfaatan Tenaga Kesehatan Warga Negara Asing di Indonesia: Perspektif Keberlanjutan Pelayanan Kesehatan - Nadisa Tiofunda Budiman (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
The phenomenon of globalization has transformed the world's landscape, connecting nations, and inspiring the concept of Special Economic Zones (SEZs). The utilization of Foreign National Health Workers (FHNWs) has become a strategy to address the shortage of medical personnel and enhance healthcare services, particularly in remote regions. However, the implementation of this policy also faces several ethical, cultural, and linguistic challenges. The ethical aspect takes center stage in the utilization of FHNWs. Patient rights, professionalism, and cross-cultural collaboration are crucial focal points in healthcare service practices. Despite its benefits, the utilization of FHNWs encounters communication hurdles, especially when the employed language is unfamiliar. Additionally, the integration of local cultural values becomes a pivotal aspect in delivering sensitive and patient-centered care. This paper analyzes policy documents related to the utilization of Foreign National Health Workers (FHNWs) in Indonesia through normative and predictive approaches. The objective is to comprehend the concepts and regulatory implementations concerning the ethics of FHNW utilization within the context of Indonesian healthcare services. The phenomena of globalization and efforts to expedite economic growth through Special Economic Zones (SEZs) have influenced these policies. The analysis involves various policy documents relevant to FHNW utilization. In facing the ethical dilemmas arising in the practice of healthcare services by foreign medical personnel, it is imperative for them to adapt to the local culture without compromising the principles of medical ethics. Moreover, competition within the job market and cultural disparities between foreign and local medical personnel also present challenges that need to be addressed. In dealing with competition, a holistic approach involving the government, relevant institutions, and professional training for local medical personnel is required. Overall, the utilization of FHNWs holds potential benefits in addressing medical workforce shortages and enhancing healthcare access. However, this utilization must be carried out with ethical responsibility, respecting patient rights, and considering cultural and professional aspects. With a prudent approach, the utilization of FHNWs can contribute to improving the quality of healthcare services and the well-being of local medical personnel, in line with ethical principles and national interests.